AB1103 Cumulative Rate and Factors Associated with Self-Reported Work Disability Among Patients with Systemic Lupus Erythematosus: Data from the Province of Cordoba, Argentina. (9th June 2015) - Lόpez Pérez, M.J.; Bertoli, A.; Alba, P.; Albiero, A.; Albiero, E.; Alessio, D.; Albarelos, A.; Asbert, P.; Astesana, P.; Audisio, M.; Benzaquén, N.; Castaños Menescardi, M.S.; et al.
Abstract : Background: SLE can inflict significant morbidity that is reflected not only in the patients' overall clinical status but also in their ability to work. Objectives: To examine the cumulative rate and factors associated with work disability in SLE patients in the Province of Cόrdoba, Argentina Methods: We studied 225 patients, age >16 years. Work disability was defined by patients' self-report of not working because of their health status. The cumulative rate of work disability was estimated with the Kaplan-Meier method. The relationship between socioeconomic-demographic, self-reported QoL (Lupus PRO) and clinical data [clinical manifestations, diagnostic criteria (1987 ACR criteria), disease activity (SELENA-SLEDAI), damage (SLICC Damage Index), co-morbidities (Charlson Index)] and work disability was examined with Chi-Square and Mann-Whitney U test. Variables with p≤0.10 in these analyses were then examined by multivariable logistic regression with work disability as the dependent variable Results: Patients were predominantly females (89%) and they had a median (IQR) age at diagnosis of 26.0 (16.0) years. Median disease duration was 96.0 (144.0) months. Fifty-five (24%) patients were work-disabled. The cumulative rate (SE) of work disability was 5% at one year, 25% at five years and 40% at 10 years. In the multivariable analysis, a lower socio-economic status (OR=1.744, 95%CI 1.063-2.861; p=0.028) and a lower QoL of life (OR=0.947, 95%CI 0.910-0, 985; p=0.07) were associated with work disability Conclusions: The cumulative rate of self-reported work disability is high among this sample of SLE patients, reaching 40% at 10 years. None of the variables related to the disease manifestations or its severity were associated with work disability. Patients of lower socio-economic status and lower self reported QoL are at higher risk of becoming work disabled. The latter would imply that any pro-active intervention directed towards preventing work disability among SLE patients in this population should have a broader approach than the disease itself Disclosure of Interest: None declared